Financing the 2004 election - Magleby, David B.; Corrado, Anthony, 1957-; Patterson, Kelly D. (Brookings Institution Press, 2006)
In the wake of recent legislation, court challenges, and demands for reform, campaign finance remains one of the most important and controversial aspects of the world's oldest democracy. Since 1960, Financing the Election volumes have presented reliable information on the costs and trends of campaign finance in the United States. In establishing the parameters of electoral campaigns and political spending-and interpreting the results-Financing the 2004 Election provides a unique resource for readers and citizens interested in the current state of politics and money in America. Financing the 20.